Detrimental effects of soluble α-synuclein oligomers at excitatory glutamatergic synapses - Ferrari, Elena; Salvadè, Michela; Zianni, Elisa; Brumana, Marta; DiLuca, Monica; Gardoni, Fabrizio (Frontiers in Aging Neuroscience, 2023)
Introduction. Oligomeric and fibrillar species of the synaptic protein α-synuclein are established key players in the pathophysiology of Parkinson’s disease and other synucleinopathies. Increasing evidence in the literature points to prefibrillar oligomers as the main cytotoxic species driving dysfunction in diverse neurotransmitter systems even at early disease stages. Of note, soluble oligomers have recently been shown to alter synaptic plasticity mechanisms at the glutamatergic cortico-striatal synapse. However, the molecular and morphological detrimental events triggered by soluble α-synuclein aggregates that ultimately lead to excitatory synaptic failure remain mostly elusive. Methods. In the present study, we aimed to clarify the effects of soluble α-synuclein oligomers (sOligo) in the pathophysiology of synucleinopathies at cortico-striatal and hippocampal excitatory synapses. To investigate early defects of the striatal synapse in vivo, sOligo were inoculated in the dorsolateral striatum of 2-month-old wild-type C57BL/6J mice, and molecular and morphological analyses were conducted 42 and 84 days post-injection. In parallel, primary cultures of rat hippocampal neurons were exposed to sOligo, and molecular and morphological analyses were performed after 7 days of treatment. Results. In vivo sOligo injection impaired the postsynaptic retention of striatal ionotropic glutamate receptors and decreased the levels of phosphorylated ERK at 84 days post-injection. These events were not correlated with morphological alterations at dendritic spines. Conversely, chronic in vitro administration of sOligo caused a significant decrease in ERK phosphorylation but did not significantly alter postsynaptic levels of ionotropic glutamate receptors or spine density in primary hippocampal neurons. Conclusions. Overall, our data indicate that sOligo are involved in pathogenic molecular changes at the striatal glutamatergic synapse, confirming the detrimental effect of these species in an in vivo synucleinopathy model. Moreover, sOligo affects the ERK signaling pathway similarly in hippocampal and striatal neurons, possibly representing an early mechanism that anticipates synaptic loss.